Connecting Analysis and Performance: A Case Study for Developing an Effective Approach - Annie Yih (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
Although theorists and performers both engage in score study, we often say that performers “interpret” and theorists “analyze” because, in general, performers are more interested in interpreting the meaning of the music, which usually involves extracting and projecting the mood, character, or drama in the music, whereas theorists focus on understanding the structure of the music. Recognizing that there is need for connecting the practices of analysis and performance, the author suggests developing an effective approach to this concern. It is proposed that both theorists and performers understand structure as process, and that this particular process expresses the unfolding of (what are called) the “structural effects” of a work’s musical events. It is argued that these structural effects are what Schenker’s analytic methods can represent (or, better yet, express). Chopin’s Prelude in E Minor, Op. 28/4, is employed as a case study, because it is brief and exemplary of a number of features for the interpretation of—or for expressing—the music’s structural effects. It is hoped that this effective approach, applied to understanding “structural effects,” will provide the kinds of performative information useful for making phrasing decisions. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part IV).